The Digitalization of the Tax System and Literacy to Increase Taxpayer Compliance - Gabrini Anggojo Jebarus; Ratih Dewi Titisari Haryana (Journal of Creative Power and Ambition (JCPA), 2026)
This study was motivated by the need to improve taxpayer compliance in Manggarai Regency amid geographical challenges and the ongoing digital transformation of public services. The digitalization of the tax system and the enhancement of digital literacy are considered strategic instruments to increase tax compliance and strengthen regional fiscal capacity. Therefore, this research aims to analyze the influence of tax system digitalization and digital literacy on taxpayer compliance in Manggarai Regency. The study employed a quantitative approach with a descriptive-associative design. Data were collected through questionnaires distributed to registered taxpayers using purposive sampling techniques. The collected data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The findings indicate that tax system digitalization significantly improves taxpayer compliance by reducing administrative barriers, increasing accessibility, and enhancing transparency in tax services. Furthermore, digital literacy was found to play a crucial role in enabling taxpayers to effectively utilize digital tax platforms and fostering trust in government services. The results also reveal a positive interaction between tax system digitalization and digital literacy, indicating that technological innovation becomes more effective when supported by adequate user competencies. In conclusion, taxpayer compliance in Manggarai Regency is strongly influenced by the synergy between a reliable digital tax system and taxpayers’ digital literacy levels.